Record-High Work-Function p-Type CuBiP2 Se6 Atomic Layers for High-Photoresponse van der Waals Vertical Heterostructure Phototransistor - He, Wei (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.